Kepastian Hukum Sertifikat Hak Pengelolaan Atas Tanah Ulayat Adat Di Kota Sungai Penuh Jambi: Kajian Yuridis-Empiris Atas Implementasi Peraturan Menteri ATR/BPN Nomor 14 Tahun 2024 - Ilham Abdi Prawira; Vioni Saputri (Jambura Journal Civic Education, 2026)
This study examines the implementation of Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) No. 14 of 2024, which strengthens the legal status of ulayat land through land registration and the issuance of Management Rights Certificates. The legal issue arises from the concerns of Indigenous communities in Sungai Penuh City regarding the potential disharmony between state land administration and the communal land tenure system of Indigenous communities (ajun arah), as well as the possibility of rights misuse. This study analyzes the certification mechanism of Management Rights, examines the legal certainty provided by the policy, and explores the perceptions of customary leaders toward its implementation. Using an empirical juridical approach through observation, interviews, and documentation, this study finds that Management Rights Certificates in Sungai Penuh City provide three dimensions of legal certainty. First, they provide certainty of status by serving as formal state recognition of ulayat land. Second, they provide certainty of control by affirming the role of customary institutions, namely Depati and Ninik Mamak, as holders of authority. Third, they provide administrative certainty through the digitalization of land data as an effort to mitigate potential disputes.The findings indicate that Management Rights have significant potential to strengthen the legality of ulayat land, provided that their implementation is based on customary consent, particularly the principle of free, prior, and informed consent, so that the existence of communal rights is not diminished. The contribution of this study lies in strengthening a model of legal protection that synergizes state law and customary law in order to preserve the socio-cultural identity of the Indigenous communities of Sungai Penuh.